2006
DOI: 10.1038/sj.ejhg.5201718
|View full text |Cite
|
Sign up to set email alerts
|

Towards mapping phenotypical traits in 18p− syndrome by array-based comparative genomic hybridisation and fluorescent in situ hybridisation

Abstract: Molecular karyotyping holds the promise of improving genotype -phenotype correlations for frequent chromosome conditions such as the 18pÀ syndrome. In spite of more than 150 reported cases with deletions in 18p, no reliable phenotype map for the characteristic clinical findings such as mental retardation, post-natal growth retardation and typical facial features has been established yet. Here, we report on four patients with partial monosomy 18p of different sizes owing to unbalanced translocations that were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
3
38
0
3
Order By: Relevance
“…Thirty-nine cases have been reported, all but two cases [Zumel et al, 1989;Molina-Gomes et al, 2006] diagnosed postnatally. Most partial trisomies result from reciprocal translocation [Taylor et al, 1976;Marcus et al, 1979;Funderburk et al, 1983;Lurie et al, 1985;Vamos et al, 1985;Zumel et al, 1989;Grammatico et al, 1992;LeChien et al, 1994;Belin et al, 1999;Oppenheimer et al, 2000;Wieczorek et al, 2003;Thomas et al, 2004;T€ umer et al, 2005;Brenk et al, 2007]. In a few cases, trisomy 20p results from parental inversion [Lucas et al, 1985;Bown et al, 1986;Molina-Gomes et al, 2006;Chaabouni et al, 2007] or the formation of isochromosomes [Sidwell et al, 2000].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Thirty-nine cases have been reported, all but two cases [Zumel et al, 1989;Molina-Gomes et al, 2006] diagnosed postnatally. Most partial trisomies result from reciprocal translocation [Taylor et al, 1976;Marcus et al, 1979;Funderburk et al, 1983;Lurie et al, 1985;Vamos et al, 1985;Zumel et al, 1989;Grammatico et al, 1992;LeChien et al, 1994;Belin et al, 1999;Oppenheimer et al, 2000;Wieczorek et al, 2003;Thomas et al, 2004;T€ umer et al, 2005;Brenk et al, 2007]. In a few cases, trisomy 20p results from parental inversion [Lucas et al, 1985;Bown et al, 1986;Molina-Gomes et al, 2006;Chaabouni et al, 2007] or the formation of isochromosomes [Sidwell et al, 2000].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Mental retardation is found in case reports of all three abnormalities (18p-, 18q-, and 18p tetrasomy), and in one study was estimated at 68% of all 18q deletion subjects [Semrud-Clikeman et al, 2005]. Abnormal EEG findings and epilepsy have been described in case reports for all three chromosomal disorders [Chudley et al, 1974;Wilson et al, 1979;Wilson and Al Saadi, 1989;Schinzel et al, 1991;Chudley et al, 1992;Krasikov et al, 1992;Poissonnier et al, 1992;Engelen et al, 1998;Tinkle et al, 2003;Linnankivi et al, 2006;Swingle et al, 2006;Brenk et al, 2007;Cody et al, 2007]. Many subjects with 18p or 18q deletions display delayed speech, mutism, or articulation difficulties [Thompson et al, 1986;Poissonnier et al, 1992;Grosso et al, 1999;Babovic-Vuksanovic et al, 2004;Wester et al, 2006;Brenk et al, 2007;Cody et al, 2007] and there has been one report of short Neuropsychiatric Genetics attention span in three out of three 18p-subjects [Thompson et al, 1986].…”
mentioning
confidence: 96%
“…22,23 Mejia-Baltodano et al 18 also reported a patient with minor dysmorphic features, small stature and obesity. Learning difficulty was noticed only after the first year of primary school and a cognitive delay of 2 years was recorded by psychometric testing at 8 years.…”
Section: Child With Segmental Uniparental Disomy 18mentioning
confidence: 97%